ChemInform Abstract: Structure of the Calcium Pyrophosphate Monohydrate Phase (Ca2P2O7·H2O): Towards Understanding the Dehydration Process in Calcium Pyrophosphate Hydrates. Issue 43 (21st October 2014) - Gras, Pierre; Ratel‐Ramond, Nicolas; Teychene, Sebastien; Rey, Christian; Elkaim, Erik; Biscans, Beatrice; Sarda, Stephanie; Combes, Christele
Abstract Single crystals of Ca2P2O7·H2O are prepared by diffusion of separate aqueous CaCl2 and Na4P2O7 solutions into a Na2SiO3·5H2O gel (room temperature, 14 d).